Capacidade antioxidante total do plasma: associações com componentes do risco cardiometabólico e consumo alimentar em jovens não obesos e clinicamente saudáveis - Costa, Jamille Oliveira (2015)
The oxidative biomarkers play an important role in the genesis of cardiometabolic risk related processes. This study aimed to investigate in clinically healthy young non-obese subjects, the total antioxidant capacity of plasma and its possible associations with anthropometric, body composition, clinical, biochemical and dietary related to cardiometabolic risk. This study evaluated individuals between the ages of 18 and 25 y, of two college of the state of Sergipe. Anthropometric parameters and body composition were measured using standardized techniques and previously described in the literature. Mechanical sphygmomanometer mercury column was used for the measurement of systolic and diastolic pressure. After fasting for 12 hours, by venipuncture, blood samples were collected to make biochemical parameters analysis and plasma antioxidant capacity. The samples (serum and plasma) were conditioned at -80°C until assay. Serum glucose, total cholesterol, high density lipoprotein, triglycerides and total antioxidant capacity plasma was evaluated by colorimetric or turbidimetric assays. The daily dietary intake was assessed by food frequency questionnaire semi-quantitative. Comparisons between groups categorized by the 25th percentile of total antioxidant capacity plasma were performed using the Mann-Whitney- U test for numerical variables. The Spearman correlation were used to track the between total antioxidant capacity plasma and other variables. The results were presented as mean ± SD or absolute frequency and relative. The confidence interval was 95% and the level of statistical significance of 5%. The study included 139 subjects with a mean age of 21,4 ± 1,9 years, with 77% belonging to the female sex. There was no statistical difference between the groups established by percentile value 25th (2,635 mM) of the distribution of CAT using established groups. Regarding the components of cardiometabolic risk almost 25% of the sample had more than one component, 7.9% over two and 0.7% more than three, the most prevalent being reduced HDL cholesterol (15%). The value of CAT did not differ between the groups for the components of cardiometabolic risk. With regard to nutrient intake, individuals showed higher CAT less of trans fat consumption values, vitamin D, iodine and zinc. Inadequacies in energy intake, saturated fat, fiber, and vitamin D were substantial though not significant. There was no statistical difference to the daily dietary intake of any food groups according to the categorization of CAT. The CAT plasma was positively correlated with the PCSI variables (r =0,15, p =0,04) and glucose (r = 0,15, p = 0,03) and negatively with SBP (-0,18, p = 0,01). In the case of young people, non-obese and clinically healthy, unlike what occurs in people with diseases already installed the CAT was unable to predict the components of cardiometabolic risk, possibly because of the introduction of active compensatory mechanism in physiological conditions.